IIB matrix model: Emergent spacetime from the master field - Klinkhamer, F R (Progress of theoretical and experimental physics, 2021)
Abstract We argue that the large-$N$ master field of the Lorentzian IIB matrix model can give the points and metric of a classical spacetime.